2009
DOI: 10.1007/s12032-009-9284-y
|View full text |Cite
|
Sign up to set email alerts
|

Imatinib mesylate-induced acute liver failure in a patient with gastrointestinal stromal tumors

Abstract: Imatinib mesylate is a drug that has been approved for treatment of chronic myeloid leukemia, Philadelphia-positive acute lymphoblastic leukemia, and advanced gastrointestinal stromal tumors. Several cases of hepatotoxicity, including fatal liver failure, have been reported with the long-term use of imatinib mesylate. Generally hepatotoxicity resolves after discontinuation of imatinib. Despite discontinuation of imatinib, hepatotoxicity can be progressive. Steroid may be useful in these patients and should be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 17 publications
1
45
0
1
Order By: Relevance
“…[14,17] In patients with severely abnormal liver function tests associated with lapatinib, imatinib and erlotinib, liver biopsies mostly showed diffuse portal-to-portal, portal-tocentral and centrilobular necrosis, inflammation and interface hepatitis. [64,76,77,78] Yet, cholestatic injury has also been reported with imatinib. [33,79] Imatinib-induced hepatotoxicity has also been shown progress to cirrhosis with portal hypertension, months after LFTs had normalised.…”
Section: Mechanisms Of Hepatotoxicitymentioning
confidence: 99%
“…[14,17] In patients with severely abnormal liver function tests associated with lapatinib, imatinib and erlotinib, liver biopsies mostly showed diffuse portal-to-portal, portal-tocentral and centrilobular necrosis, inflammation and interface hepatitis. [64,76,77,78] Yet, cholestatic injury has also been reported with imatinib. [33,79] Imatinib-induced hepatotoxicity has also been shown progress to cirrhosis with portal hypertension, months after LFTs had normalised.…”
Section: Mechanisms Of Hepatotoxicitymentioning
confidence: 99%
“…Ainsi, quatre des cinq patients de l'équipe de Ferrero et al, de même que le patient de Tonyali et al, ont eu une nette amélioration des taux de transaminases sous corticothérapie [13,14]. La réintroduc-tion de l'imatinib, associée à un corticoïde, n'a pas été suivie d'une récidive parmi les cas de Ferrero et al, ouvrant de nouvelles perspectives thérapeutiques [13].…”
Section: Discussionunclassified
“…Furthermore, the possible risk of increased RM formation through enzyme induction would have to be carefully considered. A previous study conducted by our group demonstrated an increase in risk of hepatotoxicity with the concomitant use of lapatinib and dexamethasone [53], which [59] IMA Treatment Prednisolone 100 mg/day 3 days [44] IMA Treatment Prednisolone 0.8 mg/kg/day 2 months [56] IMA Prevention Prednisolone 25 mg/day 5 months [45] IMA Prevention Prednisolone 25 mg/day 2 months [48] IMA Prevention Prednisolone 20 mg/day N.A. [49] IMA Prevention Prednisolone 50 mg/day N.A [50] IMA Treatment and prevention Prednisolone 1 mg/kg/day 6 months [46] IMA Treatment and prevention Prednisolone (T) 1 mg/kg/day (P) 30 mg/day* N.A.…”
Section: Expert Opinionmentioning
confidence: 96%